The Treatment Role of Anti-aggregants and Anti-coagulants in Radial Artery Occlusion after Transradial Coronary Angiography - NADİR, AYDIN; Nadir A.; ULUGANYAN, MAHMUT; Uluganyan M. (My University, 2023)
Objective: The transradial approach (TRA) has been widely used for coronary procedures. The rate of complications such as bleeding, hematoma and pseudoaneurysm is reduced with TRA. The purpose of this study is to search the treatment role of anti-aggregants and low molecular weight heparins (LMWH) in situation of radial artery occlusion (RAO). Methods: A total of 239 patients (140 men, 58.6%) were included. Of the patients 159 (66.5%) were elective, and 80 (33.5%) had acute coronary syndrome. When RAO was detected, patients were treated with 2 weeks of LMWH. Results: In 23 (9.6%) of 239 patients, RAO was observed. From the 23 patients with RAO, 12 (52.8%) were using anti-aggregants, and the remaining 11 (47.8%) did not use. In terms of RAO, a statistically significant difference was observed between antiaggregant users and non-users (p<0.001). In the group using antiaggregants and LMWH a statistically significant improvement was observed in the radial flow compared with the group treated withLMWH alone (p<0.001). Conclusion: In the present study, we showed that the addition of anti-aggregants to anti-coagulants decreased RAO rate, declined the symptoms of RAO, also potentiated the effects of anti-coagulants and resulted in better recanalization rate of RAO
Keywords: Sağlık Bilimleri; Health Sciences; Klinik Tıp (MED); Clinical Medicine (MED); Transradial angiography; radial artery occlusion; low molecular weight heparin; anti-aggregant